Al2O3/reduced graphene oxide double-layer radiative coating for efficient heat dissipation. (5th November 2018) - Zou, Yongchun; Wang, Yaming; Zhang, Huijuan; Wei, Daqing; Jin, Tao; Wang, Haowei; Liao, Shengzhi; Jia, Dechang; Zhou, Yu
Abstract: In this work, a double-layer radiative coating was designed, and its radiative heat dissipation performance was studied theoretically and experimentally. The duplex coating was fabricated by assembling reduced graphene oxide (rGO) on Al2 O3 bottom layer. The effects of Al2 O3 /rGO coatings on thermal radiation, heat dissipation and anti-corrosion properties of light emitting diode (LED) were investigated. The Al2 O3 /rGO radiative coating promoted the infrared emissivity value from 0.1 (bare aluminum radiator) to 0.57 at 3–8 μm and 0.83 at 8–20 μm waveband range, respectively. The double-layer coated aluminum alloy with high emissivity value enabled a significant 1 W LED temperature drop by 5.6 °C, which was coincident with the result by simulation (1 W). More remarkable, the temperature drop further decreases to 14.0 °C for 5 W LED chip. In addition, the Al2 O3 /rGO duplex coating exhibited superior hydrophobic and anti-corrosion properties, which is expected to be a promising candidate for heat dissipation of electronic products serving in oceans and humid ambient. Graphical abstract: Unlabelled Image Highlights: A novel Al2 O3 /reduced graphene oxide double-layer radiative coating was designed for efficient heat dissipation. The double-layer coating was fabricated by assembling reduced graphene oxide on Al2 O3 bottom layer. The high emissivity double-layer coating enabled a significant LED temperature drop. The duplex coating showed superior hydrophobic and anti-corrosion properties.